Usefulness of Digital Language Resources in Improving Native Language among Adults - Suzana Žilič Fišer; Jani Pavlič; Ines Kožuh (Applied Sciences, 2022)
Important keys to effective communication are language competences, which can be supported by using digital language resources. These usually assist the acquisition of a second language, despite their potential for improving one’s native language. Our study was, thus, aimed at raising awareness about the possibilities of improving the native language of an adult population by using digital language resources for the Slovenian language. We conducted workshops, a survey and, partly, semi-structured interviews with 124 participants. We examined whether the perceived usefulness and ease of using digital language resources depends on age, education, self-assessed language proficiency, and experience with language training. The analysis revealed that self-initiative use of analogue language resources is related positively to using digital ones for seeking information, improving language use, as well as for study or work. Moreover, self-assessed proficiency in language was found to affect the perceived ease of using digital language resources. These findings may help language professionals support developing language skills by using digital language resources and preserving language in an adult population.